Effect of the Oral Probiotics on Salivary Alpha-amylase, Buffering Capacity, pH, and Plaque Level among Dental Students – A Pilot Randomized Controlled Trial - S. Savitha Priyadarsini; Kamlesh Manohar Palandurkar; P. G. Naveen Kumar; Mahesh R. Khairnar; Zainab Akram; Ridhi Ghodela; Sachin Kumar Jadhav; Neha Shukla (Journal of Indian Association of Public Health Dentistry)
Background: Saliva has been used as a potential diagnostic tool due to its ease, noninvasive accessibility, along with its numerous biomarkers. The use of salivary alpha amylase (SAA) as a biomarker for various diseases including carious lesion is a subject of intense discussion. The objective of the study is to evaluate the effect of the consumption of oral probiotics on SAA, buffering capacity, pH, and plaque level among dental students. Materials and Methods: This parallel-arm, double-blinded randomized controlled trial was conducted for a period of 5 days on 20 randomly selected dental students allocated into two groups – enKor D and ProGG probiotics, ten in each group. Saliva samples were collected at baseline and after probiotics usage for 5 days for the analysis of SAA by Liquixx Amylase kit, buffering capacity and pH by pH digital meter, and plaque level assessed by Silness and Loe plaque index. Results: The results of the study showed that there is no difference in the level of SAA in both the groups enKor D and ProGG after the consumption of probiotics for 5 days (P = 0.062 and 0.086, respectively). Buffering capacity and pH remained in the normal range in both the groups with no significant changes. Conclusion: It was concluded that the oral probiotics do not show any effect on the SAA level, which facilitates acid production by starch hydrolysis and plaque formation.